Relationship between textural properties and sensory qualities of cookies made from medium- and long-chain triacylglycerol-enriched margarines - Arifin N.; Peng K.S.; Long K.; Ping T.C.; Yusoff M.S.A.; Aini I.N.; Ming L.O. (2024)
Indexed by WOS/ Scopus